The Application Of Online Presence To The Work Discipline Of Purwakarta State Court Employees - Bunga Rosalia; Aji Tuhagana; Nandang (Enrichment : Journal of Management, 2022)
Civil Servants (PNS) as state apparatus, among others, are shown by their ability to achieve performance and work discipline. Civil servants must have a high discipline good performance and attitudes and behavior that are full of obedience and obedience to the state. District Court Purwakarta currently uses manual attendance to record and return employees then uses a recapitulation of adjustments with an online presence to calculate or determine the level of employee performance. The researcher gave the title ‘’The Application Of Online Presence To The Work Discipline Of Purwakarta State Court Employees’’ This research is descriptive and qualitative. The results of the study show that this online attendance will minimize the spread of the virus during this pandemic, there is no need to queue when absent. This attendance system also does not make employees make changes to their habits, employees who initiate such as doing attendance at home and when manual absences do not match the time with absences in the application.